Investigation of the relationship between transactional analysis ego states and treatment compliance of individuals with substance use disorder - Altun, Ozlem Sahin; Karakas, Sibel Asi; Ersogutcu, Filiz (Taylor & Francis Inc, 2022)
Aim This study was conducted to examine the relationship between transactional analysis ego states and treatment compliance of individuals diagnosed with SUD(substance use disorder). Materials and Methods This cross-sectional and descriptive study was conducted between January and June 2018 with 132 individuals diagnosed with SUD at the a Mental Health and Diseases Hospital AMATEM (Alcohol and Drug Addiction Research and Treatment Center) unit. Data were collected using the Personal Information Form, the Ego States Scale and the Morisky Medication Adherence Scale. SPSS program was used to evaluate the data. Results Mean scores of the Ego States Scale subscales of the participants were 0.16 +/- 0.02 for the Critical Parent subscale, 0.23 +/- 0.01 for the Nurturing Parent subscale, 0.21 +/- 0.01 for the Adult subscale, 0.19 +/- 0.02 for the Adapted Child subscale and 0.19 +/- 0.27 for the Natural Child subscale. The mean score of the participants' Medication Adherence Scale was found to be 1.66 +/- 0.27. No statistically significant relationship was found between treatment compliance and ego states (p > .005). Conclusion In this study, it was found that the participants mainly used Adult and Nurturing Parent ego states and their level of treatment compliance was moderate.
Keywords: Nursing; substance use disorder; treatment compliance; transactional analysis ego states